Liposomal bupivacaine infiltration for postprocedural analgesia following interventional procedures for vascular anomalies - Mohammad A. Amarneh, MD; Kyung Kim, MD; Raja Shaikh, MD; Cindy L. Kerr, CPNP; Horacio Padua, MD; Gulraiz Chaudry, MB, ChB; Ahmad I. Alomari, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
We describe the use and assess the safety of liposomal bupivacaine (LB) infiltration for prolonged postprocedural analgesia after procedures to treat vascular anomalies. This is a single-center prospective study. Consecutive patients aged ≥6 years undergoing painful interventions for vascular anomalies were included. Data collected included patient demographics, diagnosis, procedure details, LB dosage, periprocedural pain levels, side effects, and the use of additional analgesics. Follow-up extended through postprocedural day 5. LB was used in 26 procedures in 24 patients with mean age of 17.0 years (range, 6.0-33.0 years; median, 17.5 years). One patient was excluded owing to a lack of follow-up. Twenty patients did not require any pain medication in the recovery unit. The mean pain level was 4, 2, 2, and 2 on postoperative days 1, 2, 3, and 5, respectively. No side effects were noted. LB proved to be a safe and likely effective local anesthetic agent, providing prolonged postprocedural analgesia for patients undergoing painful treatments for vascular anomalies.